1979
DOI: 10.1111/j.1463-6409.1979.tb00614.x
|View full text |Cite
|
Sign up to set email alerts
|

Two Types of Nematocysts in Campanulariidae (Cnidaria, Hydrozoa) Studied by Light and Scanning Electron Microscopy

Abstract: The cnidom was found to consist of several morphologically distinct types of nematocysts in six investigated species of Campanulariidae. Descriptions are provided for b‐rhabdoids (micro‐basic b‐mastigophores) of two sizes, occurring in the polyps of Campunulariu Integra and Clytia hemisphaerica of the johnstoni and gracilis forms, respectively. The smaller nemato‐cyst is the most frequent type and is also abundant in the polyps of Laomedea flexuosa, L. geniculata, L. longissima and L. dichotoma as well as in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
2

Year Published

1982
1982
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 13 publications
0
13
0
2
Order By: Relevance
“…Despite this, these characters form the primary basis for species descriptions in the Campanulariidae. Alternatively, morphological characteristics of the nematocysts, or stinging capsules, can be taxonomically useful in many groups of hydroids, including campanulariids (Ostman, 1979;Gravier-Bonnet, 1987;. But again, some nematocyst characters may be plastic and they are time consuming and require live material to study.…”
Section: Taxonomymentioning
confidence: 99%
See 1 more Smart Citation
“…Despite this, these characters form the primary basis for species descriptions in the Campanulariidae. Alternatively, morphological characteristics of the nematocysts, or stinging capsules, can be taxonomically useful in many groups of hydroids, including campanulariids (Ostman, 1979;Gravier-Bonnet, 1987;. But again, some nematocyst characters may be plastic and they are time consuming and require live material to study.…”
Section: Taxonomymentioning
confidence: 99%
“…Ostman (1979;Ostman et al, 1987; has characterized nematocysts of Campanulariid hydroids, and found species-specific differences.…”
Section: Taxonomic Charactersmentioning
confidence: 99%
“…Cnidomes have been studied in detail for some hydrozoans, and many reviews corroborate the taxonomic relevance of these observations (e.g., Östman, 1979a, 1979b, 1982Cornelius & Östman, 1987;Gravier-Bonnet, 1987;Marques et al, 2000;Marques, 2001;Peña Cantero et al, 2007), as well for Scyphozoa (viz. Calder, 1971 and Cubozoa (e.g., .…”
Section: Introductionmentioning
confidence: 88%
“…A compilação de informações acerca do tamanho e distribuição dos nematocistos ultrapassa um século (Bedot, 1896;, mas somente trabalhos mais recentes utilizaram os diferentes tipos de cnidas para propor relações filogenéticas entre as classes de Cnidaria e entre os componentes dessas classes . O cnidoma tem sido estudado detalhadamente em Hydrozoa, e muitos estudos corroboram a importância taxonômica dessas observações (Östman, 1979a, 1979b, 1982Cornelius & Östman, 1987;Gravier-Bonnet, 1987;Marques et al, 2000;Marques, 2001;Peña Cantero et al, 2007), o que também foi demonstrado para Scyphozoa (viz. Calder 1971 e Cubozoa .…”
Section: Taxonomia De Staurozoa: Dados Morfológicos Histológicos E Dunclassified
“…Muitos estudos demonstraram a importância da análise dos nematocistos e sua morfometria na delimitação de gêneros e espécies em Campanulariidae (Östman, 1979a, 1979bCornelius & Östman, 1987;Lindner & Migotto, 2001), padrão este aqui corroborado. A diferença no comprimento dos nematocistos microbásicos mastigóforos tipo B de Campanularia e Orthopyxis é evidente, com aproximadamente 6µm de variação, constituindo uma importante característica diagnóstica para os gêneros na área de estudo, embora a avaliação de um maior número de espécies de Campanularia seja desejável para corroborar esta hipótese.…”
Section: Variabilidade Morfológica De Orthopyxisunclassified